How China's New Silk Road Threatens European Trade. Issue 1 (2nd January 2017) - Holslag, Jonathan
Abstract: For all the promises of mutually beneficial cooperation, Chinese policy documents about the New Silk Road, also called 'One Belt, One Road', mostly testify to a strong ambition to unlock foreign markets and support domestic firms in taking on foreign competitors. This confirms China's shift from defensive mercantilism, which aims to protect the home market, towards offensive mercantilism, which seeks to gain market shares abroad. In a context of global economic stagnation, this comes as a major challenge to Europe. As China's market share grows spectacularly in countries along the New Silk Road, key European member states have both lost market shares and even seen their exports shrink in absolute terms.